The Synergy of Local Government and Academia in Addressing Peatland Fires in Siak Regency with a Technology-Based Approach - Diki Arisandi; Amir Syamsuadi; liza Trisnawati (GoAcademica Research & Publishing, 2023)
This study aims to explore the synergy between the local government and academia in mitigating peatland fires in Siak Regency. In the fields of social humanities, science, and technology, this study uses an exploratory qualitative method. The study reveals the important role of the local government in disaster mitigation through regional regulations, policies, and synergy between related departments. Through the regional regulation on forest fire prevention and handling, the local government has involved the Regional Disaster Management Agency (BPBD) and other supporting units in mitigation efforts. In addition, academics have also contributed by developing a technology-based peatland fire detection system. The main results of this study show that collaboration between the local government and academia is very significant in peatland fire mitigation efforts. The role of the local government through Governor's Decree No. 9 of 2020 and Regent's Decree No. 4 of 2022, as well as synergy between departments, encourages more effective steps in preventing and handling peatland fires. In addition, the contribution of academics to producing a technology-based peatland fire mitigation technology design opens up the potential for innovative and sustainable solutions. These findings have significant implications, as they highlight the importance of collaboration between the local government and academia in facing the challenges of peatland fire mitigation in Siak Regency. This synergy allows a better understanding of the problem, the development of more effective policies, and the application of advanced technology in preventing and handling peatland fires.